Estrutura discursiva da notícia : revisão e aplicação de um modelo - Santana Sobrinho, Márcio (2011)
This work aims to review the series of studies on the superstructure of news made by the Dutch linguist Teun van Dijk (News as discourse, 1980, until Schemata News, 1986) so, afterwards, to draw an analysis of 24 newspaper articles produced by the Press Office at the Universidade Federal de Sergipe (Ascom-UFS) during 2009 in order to see how they were constructed in terms of categories chosen to propose and seek improvements. From our analysis, one can notice a strong use of "lead" supported in the "comments", one realizes that the "main event", the core of news reporting, the journalist is hierarchical, and as a change in their order can change the facts, in the "background" one can see the incorporation of the researcher thoughts through the inclusion of methodological steps, yet in that category, there is the lack of a "historic" depth; it is also analyzed a positive and a negative for the use of "consequences / reactions." At the end, this work refers, slightly, about the forms of reproduction by which the local press uses the texts produced in local Ascom, seeking to identify three types of harmful behaviors.